Designing Standard Operating Procedure (SOP) for Planning and Implementing Machine Maintenance for the Implementation of ISO 9001:2015 Clause 7.1.3 using the Business Process Management (BPM) Method in Hijab Printing Production - Rahmi Anugrah Kunanti; Wiyono Wiyono; Sheila Amalia Salma (JTI: Jurnal Teknik Industri, 2024)
Maintenance management is important for production companies that rely on machines as the main infrastructure. UMKM Meflanna, as a printed hijab producer, has not managed machine maintenance routinely and effectively, which impacts the cessation of the production process and the failure to achieve several production targets. This study aims to compile a Standard Operating Procedure (SOP) for planning and implementing machine maintenance using the Business Process Management (BPM) method. The BPI method supports business process improvement by analysing the gap between actual conditions and the requirements of ISO 9001:2015 clause 7.1.3, which is the basis for designing process improvements. This study produces an SOP for Machine Maintenance Planning and Implementation, which includes preventive maintenance planning procedures and corrective and preventive maintenance implementation. It also provides supporting forms to document maintenance information. With structured procedures and better documentation, UMKM Meflanna is expected to maintain production continuity and achieve the set targets. Keywords: Business Process Management (BPM), ISO 9001:2015 clause 7.1.3, maintenance management, Standard Operating Procedure (SOP)